THE HERMENEUTICS OF AL-SYAUKANI: THE GRAVE AND THE BARZAKH IN FATḤ AL-QADĪR - Maryono, Maryono; Ridwan, Muhammad; Yusyama, Asep Yana (Peminat Ilmu Ushuluddin, 2024)
This article aims to examine Al-Shawkani's interpretation in Al-Shawkani's hermeneutic theory in Tafsir Fathkhul Qadir eschatological verses as well as the implications of the theory and its application to various categorization models of interpretation studies. Using a qualitative literature methodology, it was found that Al-Shawkani's hermeneutics was applied to verses about the graves and the barzakh. This study produces conclusions. First, al-Shawkānī's hermeneutics is built on the principle of convergence between riwāyah and dirāyah. Viewed from the perspective of triadic structures in hermeneutics,